Rapid Flood Inundation Mapping Using Multi-Temporal Sentinel-1 SAR: An Example from Kendari City - Septianto Aldiansyah; Randi Adrian Saputra; Khalil Abdul Wahid; Ilyas Madani; Duwi Setiyo Wigati Ningsih (Department of Geophysical Engineering, Faculty of Engineering, University of Lampung, 2024)
Information regarding flood inundation presented through maps provides valuable information in preparedness and flood mitigation efforts when a disaster occurs by utilizing the potential of satellite imagery. This study aims to map flood inundation areas by integrating Sentinel-1 Synthetic Aperture Radar (SAR) data and the Otsu method. The results were validated with a confusion matrix and compared water areas that were flooded (March 2022), not flooded (February 2022), and flood seasons in previous years (April 2017 and June 2018). Historical patterns of rainfall are also analyzed to understand flood events. The overall accuracy and Kappa coefficient of the 22 March 2022 flood inundation map are 95.81% and 0.86, respectively. Areas that are submerged (region under water) classify floods well compared to areas that are not flooded (February 2022). Classification results in April 2017 and June 2018 also show the same thing. Sentinel-1 SAR which is integrated with the Otsu method in GEE can map flood inundation areas quickly and in Near-real time and increase the existing possibilities to save the grassroots and community's economic resources and protect infrastructure.